Surgical outcome of unilateral recess-resect in convergence insufficiency-type intermittent exotropia: Comparison of two surgical formulae - Hye Jun Joo; Hyeon Jung Kim; Dong Gyu Choi (PLoS ONE, 2026)
Aim We compared the surgical outcomes of monocular lateral rectus recession–medial rectus resection (RR) for convergence insufficiency-type intermittent exotropia (CI-type IXT) using two different formulas. Methods A retrospective review of patients who underwent unilateral RR for CI-type IXT with at least 6 months follow-up was done. In group 1 (58 patients), RR was determined based on the average of distance and near exodeviation. In group 2 (80 patients), lateral rectus (LR) recession amount was based on the exodeviation at distance and medial rectus (MR) resection was done as the same amount of LR recession (symmetric RR). Results Group 2 showed greater esodeviation at distance and near until postoperative 1 month, however, there was no significant difference in deviation angles between the two groups from 3 to 24 months. Both groups showed significant reduction in near-distance difference up to postoperative 24 months (p < 0.05): from 8.3 PD preoperatively to 1.0 at 24 months in group 1 and from 9.3 to 3.8 in group 2. The success rate at 24 months was 72.7% and 67.6% in group 1 and 2, respectively (p = 0.795). Conclusion RR based on the average of distance and near exodeviation and the symmetric RR can successfully collapse the near–distance difference while achieving favorable surgical outcomes.